2004
DOI: 10.1021/la035517d
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Various Silicone Oil/Water Emulsion Films as a Function of Surfactant and Salt Concentration

Abstract: There have been reports, originally by the Bristol group, and subsequently by others, of the preparation and properties of emulsions of stable, nearly monodisperse droplets of poly(dimethylsiloxane) (PDMS) in water, where no added surfactant is used. It has been assumed that their stability is due to the high density of surface-ionized hydroxyl groups, similar in fact to the closely related Stöber silica particles. In this study we confirm, from droplet lifetime studies, that droplets, prepared from such synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
37
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 41 publications
(79 reference statements)
2
37
3
Order By: Relevance
“…Zeta measurements showed that emulsions were negatively charged, with zeta potential values as low as À62 mV (Figure S4), in agreement with Vincent's recent study. [11] Polymer Characterization…”
Section: Colloidal Aspectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zeta measurements showed that emulsions were negatively charged, with zeta potential values as low as À62 mV (Figure S4), in agreement with Vincent's recent study. [11] Polymer Characterization…”
Section: Colloidal Aspectsmentioning
confidence: 99%
“…[10] Principally small cycles, typically D 4 , and linear oligomers were formed, thus generating a surprisingly very stable micron-size emulsion. The authors recently came out with an explanation for this phenomenon, [11] namely the colloidal stability is ensured by the preferential adsorption of short-linear chains bearing silanol groups at the surface at the expense of cyclics. The addition of a surfactant such as sodium dodecylsulfate (SDS) in the initial recipe only helped to improve the colloidal long term stability, but did not change basically the content of cycles and linear chains.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These core-shell particles were prepared from oil/water (O/W) emulsions containing monodisperse, surfactant-free PDMS droplets [2,3], which were encapsulated using alkoxysilanes, or mixtures of alkoxysilanes, added to the continuous aqueous phase [1,[4][5][6]. Under basic or acidic conditions an interfacial condensation reaction occurs at the PDMS/water interface, leading to silica-based shells up to $0.1 lm in thickness.…”
Section: Introductionmentioning
confidence: 99%
“…However, silicone oil significantly destabilizes emulsion due to its low interfacial tension. 5,6 Silicone surfactants show characteristic properties which make their use very attractive to the cosmetic industry. 7 One of the advantages of silicone surfactants is that the molecular weight can be readily controlled.…”
Section: Introductionmentioning
confidence: 99%